Cost analysis of a 1 MW BioGenerator, a bioelectrochemical technology for energy storage. (February 2019) - Abou Jarboua, Tariq; Davison, Matt; Karamanev, Dimitre
Highlights: A novel electrobiochemical technology, the BioGenerator, was studied. Cost analysis of a 1 MW BioGenerator was performed. It was shown that the cost of converting hydrogen to electricity is $0.12/kWh. Abstract: The first in-depth cost analysis of a bioelectrochemical technology for electrical power generation is reported in this work. The technology, named the BioGenerator, is a unique biological convertor of hydrogen to electricity to be used as a key component of the hydrogen-based energy storage. A theoretical scale-up for one MW BioGenerator was performed and comprehensive cost analysis for all of its components was conducted. It is shown that the cost of conversion of hydrogen to electricity in 1 MW BioGenerator is approximately $0.10 per KWh.